2011
DOI: 10.1002/pon.2041
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prophylactic salpingo‐oophorectomy on quality of life and psychological distress in women with a BRCA mutation

Abstract: For most women, physical and mental health-related quality of life did not deteriorate after prophylactic salpingo-oophorectomy, and they were less worried about ovarian cancer. A subset of women continued to experience moderate to severe cancer-specific distress. Identification of these women is important in order to provide continued counseling and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 30 publications
11
62
2
1
Order By: Relevance
“…In addition, the total IES-R scores were significantly lower at 1 year after surgery. This result indicated that RRSO reduced the psychological impact and burden of knowing the results of genetic testing in addition to reducing anxiety over the development of cancer (cancer-specific distress), consistent with the results of previous studies conducted overseas (15). These results suggest that RRSO effectively reduces anxiety over the future development of breast and ovarian cancer associated with BRCA1/2 mutation and its associated psychological burden.…”
Section: (250)supporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the total IES-R scores were significantly lower at 1 year after surgery. This result indicated that RRSO reduced the psychological impact and burden of knowing the results of genetic testing in addition to reducing anxiety over the development of cancer (cancer-specific distress), consistent with the results of previous studies conducted overseas (15). These results suggest that RRSO effectively reduces anxiety over the future development of breast and ovarian cancer associated with BRCA1/2 mutation and its associated psychological burden.…”
Section: (250)supporting
confidence: 89%
“…In addition, studies suggested that while reducing concerns regarding the potential development of breast or ovarian cancer, RRSO also does not adversely influence the quality of life (QOL) (14). Furthermore, it has also been shown that RRSO does not worsen the physical or psychological aspects of QOL, but reduces distress related to the risk of the development of ovarian cancer (15). In Japan, it is also considered important for patients undergoing RRSO to receive appropriate support and to minimize psychosocial damage.…”
Section: Introductionmentioning
confidence: 99%
“…General distress was comparable in women after RRSO compared to age-matched controls infrom the general population (Brief Symptom Inventory Global score 50.1 versus 50) [53]. Cancer-specific distress significantly decreased (IES from 19.2 (range 0-57) to 10.4 (range 0-53)) after RRSO but was still moderately or severely present in a moderate or severe amount in 19% of participants [53].…”
Section: Psychological Distress: Anxiety Depression and Cancer Worrymentioning
confidence: 82%
“…Our literature search yielded eight articles concerning the QoL of BRCA mutation carriers after RRSO, of which three were prospective with measurements before and until 12 months after surgery [20,52,53] and five cross-sectional [54][55][56][57][58] of which one also retrospectively evaluated the presurgical status [57], with mean follow-up durations of 6 months to 6 years. A c c e p t e d M a n u s c r i p t 17 be temporarily lower at 1 month after surgery compared to women in a surveillance group (Physical Component Summary β -5.61; p<0.02), but this difference was no more apparent after 6 and 12 months [52].…”
Section: Ovarian Cancer In Germline Brca Gene Mutation Carriersmentioning
confidence: 99%
“…107 Studies also have demonstrated lower levels of depression and anxiety. [107][108][109] After risk RRM, women report a positive emotional response related to the reduction of their breast cancer risk. 110 However, cancer worries did not appear to decrease in another study of younger female gene carriers who underwent prophylactic mastectomy and oophorectomy.…”
Section: Hbocmentioning
confidence: 99%